ENHANCING UNIVERSITY STUDENTS ENGLISH WRITING SKILLS ON CONTENT AREA - Politton, Mariana Ester; Hadiyanti, Kayetana Maria Widi (LLT Journal: A Journal on Language and Language Teaching, 2019)
Writing, as an instrument of communication, is nowadays accomplished mostly in English to ensure information understood globally via digital platforms. This creates a transformation in job fields into utilizing technologies to textually deliver messages. Therefore, it is vital to generate high qualified future employees competing in the work places. Accordingly, university students must be equipped with English writing competencies as well as strategies focusing on content area, in addition to forms, so as to promote meaning-making concerning critical and logical thinking skills, besides to comprise comprehensive realization. Thisqualitative research utilized a critical literature review by conducting in-depth data collection, organization, integration, and classification of writing strategies. It offers suggested maneuvers to overcome higher education learners writing problems: lack of content maturation practices, through implementing collaborative writing discussions with either or both verbal or / and online discussions. It can as well integrate (intensive / extensive) reading and writing instructions in contextual cognitive processes concentrating on intellectual meaning development.